Pablo Picasso In Nmw - H. Romanowski (NC, 2026)
Stanisław Lorentz guides Pablo Picasso through the National Museum in Warsaw.label QS:Len,"Stanisław Lorentz guides Pablo Picasso through the National Museum in Warsaw."label QS:Lpl,"Stanisław Lorentz oprowadza Pabla Picassa po Muzeum Narodowym Warszawie."label QS:Lfr,"Stanisław Lorentz guide Pablo Picasso par le Musée National de Varsovie."
Droits : Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie; Art